1995
DOI: 10.1017/s002193200000701x
|View full text |Cite
|
Sign up to set email alerts
|

Old Age Security and Inheritance in Nepal: Motives Versus Means

Abstract: This paper documents expectations of old age support in rural Nepal. Current living arrangements of the elderly have been analysed with a focus on the ownership of land holdings. It is argued that the intergenerational transfer of property through inheritance from the older to the younger generation, especially among sons, together with the Nepali normative prescription that sons care for their aged parents, provides a mechanism for old age support. However, land is becoming a scarce resource, cultural traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Most marriages have historically been arranged, at least in part, by parents and/or other relatives (Ghimire et al 2006). However, this practice has been loosening recently, and it is now more common than in the past for young people to participate in choosing their marriage partner (Ghimire et al 2006; Niraula 1995). …”
Section: Background and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Most marriages have historically been arranged, at least in part, by parents and/or other relatives (Ghimire et al 2006). However, this practice has been loosening recently, and it is now more common than in the past for young people to participate in choosing their marriage partner (Ghimire et al 2006; Niraula 1995). …”
Section: Background and Settingmentioning
confidence: 99%
“…In Nepal, children have an important value for their parents, both in their ability to economically contribute to the household and in their role in old-age security and Hindu religious rituals (Bose and South 2003; Niraula 1995). Like in the United States (Thornton and Young-DeMarco 2001), attitudes in Nepal are more disapproving of marital dissolution when couples have children.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In many parts of India, parents are not supposed to accept gifts or even food and drink from married daughters and their marital family members. If parents do rely on daughters for old age support it is customarily perceived as undesirable and unfortunate (Jeffery et al 1989; Karve 1965; Niraula 1995). For example, in 1990 in West Bengal, Lamb (2000: 83) found that parents who relied on daughters for old age support “incur[red] considerable loss of respect,” while Vatuk (1990:77) described it as “shameful and demeaning” in 1970s New Delhi.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 1990 in West Bengal, Lamb (2000: 83) found that parents who relied on daughters for old age support “incur[red] considerable loss of respect,” while Vatuk (1990:77) described it as “shameful and demeaning” in 1970s New Delhi. These differences between daughters' and sons' roles are also an important reason for son preference (Brijnath 2012; Dharmalingam 1994; Jeffery, Jeffery, and Lyon 1988; Jeffery and Jeffery 1997; Niraula 1995; Vatuk 1990). Having a son is the customary means of ensuring old age support.…”
Section: Introductionmentioning
confidence: 99%
“…Most marriages have historically been arranged by parents or other relatives, although it has become more common for young people to participate in choosing their spouse (Niraula 1995; Ghimire et al 2006). Like marriage, childbearing is nearly universal.…”
Section: Settingmentioning
confidence: 99%